Impact of Germination on the Edible Quality and Nutritional Properties of Brown Rice Noodles - Ruiyun Chen; Xudong Yan; Mingxi Cai; Jiamei Cai; Taotao Dai; Yunfei Liu; Jianyong Wu (Foods, 2024)
Brown rice noodles are increasingly favored by consumers for their health benefits; however, their development is hindered by their poor edible qualities. The effect of germination on the cooking, textural, organoleptic and nutritional qualities of brown rice pasta was investigated. In comparison to ungerminated brown rice noodles, germination resulted in a shorter cooking time, reduced cooking losses, and decreased hardness and adhesion of noodles as well as reduced bitter taste. These changes can be attributed to germination altering the basic composition of brown rice. Meanwhile, the contents of γ-aminobutyric acid, free phenolic acid, and bound phenolic acid increased by 53.43%, 21.71%, and 7.14%, respectively, while the content of resistant starch de-creased by 21.55%. Sprouting is a promising strategy for improving the edible quality and nutritional properties of brown rice noodles.